Improving Patient Satisfaction in the Outpatient Otolaryngology Clinic. (2nd September 2014) - Orb, Quinn T.; Wilson, Kevin F.; Meier, Jeremy D.; Error, Marc E.; Johnson, Steven; Ward, Preston D.
Abstract : Objectives: (1) Determine patient and provider factors associated with patient dissatisfaction in an otolaryngology clinic. (2) Identify strategies to improve the patient experience. Methods: Patient satisfaction surveys were prospectively collected in an academic otolaryngology clinic from January 2011 through March 2013. Patient variables (age, insurance type, established vs new patient, diagnosis, and treatability of condition) and provider variables (years in practice, subspecialty, and clinic wait time) were retrospectively analyzed to determine factors associated with patient dissatisfaction. "Treatability" was graded on a scale of 1 to 5, with diagnoses having a clear treatment option (ie, tonsillectomy for chronic tonsillitis) = 1, and diagnoses with no therapeutic options available (ie, tinnitus) = 5. Results: The cohort included 820 patient satisfaction surveys and charts. Stepwise linear regression analysis identified no single patient or provider variable associated with poor satisfaction scores. Cluster analysis evaluating the interplay between variables identified 5 unique clusters of patients. Satisfaction scores in 4 of the clusters were in the 99th percentile, while the remaining cluster ranked in the 10th percentile. This cluster consisted of a higher proportion of new patients with difficult‐to‐treat otologic conditions who described their wait time as excessive and were more likely to be self‐pay. Conclusions: Several factors influence patient satisfaction in an otolaryngology clinic. In this study, variables associated with lower patient satisfaction scores included patients with longer clinic wait times, "difficult to treat" otologic diagnoses, and new patients. Addressing the issues common in this population to better meet their needs and expectations may improve overall patient satisfaction.